Role of exercise in severe COVID-19 case - Arnengsih Nazir; Witri Septiani (Surabaya Physical Medicine and Rehabilitation Journal, 2023)
Abstract Severe COVID-19 infection can lead to prolonged recovery and troublesome symptoms. The symptoms reported in those patients were dyspnea, fatigue, weakness, anxiety, and activity intolerance. Patients showed limited exercise capacity and interfered with daily activities, as well as the quality of life. We report the role of exercise in improving activity tolerance in a survivor of a COVID-19 severe case. A male patient, 51 years, came to outpatient pulmonary rehabilitation after hospitalization due to a severe case of COVID-19. The patient had a low activity tolerance presented as fatigue, dyspnea, activity-induced oxygen desaturation, and inability to perform exercise testing, in addition to mild anxiety. A set of exercises consisting of breathing, flexibility, muscular, and cardiorespiratory endurance were given for 4 weeks along with psychological counseling. Barthel Index, cardiorespiratory fitness, sit-to-stand test, Fatigue Severity Scale, Medical Research Council Dyspnea Scale, and maximum breathing capacity were recorded as outcome measures. A Zung Self-rating Anxiety Scale and insomnia severity index were also measured. After 4 weeks, the symptoms of activity intolerance decreased. There were improvements in all outcomes except for the insomnia severity scale. Experts recommend that COVID-19 patients should carry out regular daily activities and low to moderate-intensity exercise in the first 6-8 weeks after discharge. Resuming daily physical activities as early as possible can affect functional recovery. It is also beneficial for general fitness, fatigue, emotional disturbance, and lack of confidence. In this patient, low-intensity exercises as recommended by experts were given to improve activity tolerance.